Vertigo as Initial Symptom of Cerebellar Hemorrhage in Adult Woman : A Case Report - Dessy Gita Hepsari; Novian Wibowo (Green Publisher Indonesia, 2024)
Vertigo, difficulty walking, and loss of balance/coordination are among the symptoms of stroke in 50% of stroke cases. Vertigo due to cerebrovascular disease is generally associated with other neurological signs such as cranial nerve abnormalities, hemiparesis, facial weakness, diplopia, hyperesthesia, and Horner's syndrome. A 42-year-old woman came to the emergency department with complaints of dizziness, nausea, and frequent vomiting for the previous 4 hours. The symptoms are also accompanied by a feeling of tingling on the left side of the face, and the left eyelid cannot open optimally. The patient has a history of uncontrolled hypertension. The HINTS test revealed central vertigo, and the patient also found dysdiadochokinesis, ataxia, and dysmethria. A non-contrast head CT scan showed ICH in the left cerebellum with a volume of 6.9 cc. Based on the results of these examinations, the patient was diagnosed with cerebellar hemorrhage. The blood supply to the brainstem, cerebellum, and inner ear comes from the vertebrobasilar vascular system. Blockage or rupture of blood vessels in one of the main branches of this system can cause symptoms of vertigo. Symptoms of vertebrobasilar stroke vary widely and depend on which of the three main circumferential branches is affected; posterior inferior cerebellar artery, anterior inferior cerebellar artery, or superior cerebellar artery. Vertigo in patients who have risk factors for stroke accompanied by other neurological symptoms should be considered for a thorough neurological examination to evaluate the possibility of cerebrovascular disease.